MEASURES TO PROTECT THE ENVIRONMENT FROM THE HARMFUL EFFECTS OF MOTOR TRANSPORT - Abdulatif Abdubannopov; Saidakbar Abdupattayev (European Science Publishing, 2024)
In this article, hybrid power devices, which are currently the most efficient in terms of economy and environmental parameters, are used: they work with an internal combustion engine on highways, and they work with an electric engine in urban areas, and a method of controlling the engine during idle running for cars in operation is developed using a software device implementation of cylinder deactivation according to a rational algorithm is shown.
Keywords: Cargo transportation, truck, operational conditions, construction, toxic gases, car.